Accreditation for cademic quality - Şenel, Seçil; Yalçın, Dilek (Int Scientific Conference SGEM, 14, Kilment Ohridsky BLVD, Sofia, 1797, Bulgaria, 2008)
As it is well-known, the latest trend in academia has been the rapid growth of online or distance learning courses. Globalization makes mobility easy and possible. That is why a graduate has the opportunity to find not only a nationwide but also a worldwide occupation. In most countries in the world, the function of accreditation for educational institutions is conducted by a government ministry of education. The purpose of this study is presenting the goal of the accreditation. The goal of accreditation is to ensure that education provided by institutions of higher education meets acceptable levels of quality. In order to present the educational philosophy that monitors the international values and standards, ABET (Accreditation Board for Engineering and Technology) in engineering education and international standards in medical education are taken into consideration. Engineering departments of a few universities have been accredited with respect to the ABET criteria. In medical education a few universities have been initiating the accreditation process in Turkey. In this study, the accreditation and assessment methods in higher education are discussed.
Keywords: Accreditation; Higher Education; Abet Criteria; Quality İmprovement